Optical Resonance of A Three-Level System in Semiconductor Quantum Dots - Nguyen Van Hieu; Nguyen Bich Ha (ASEAN Journal on Science and Technology for Development, 2006)
The optical resonance of a three-level system of the strongly correlated electrons in the twolevel semiconductor quantum dot interacting with the linearly polarized monochromatic electromagnetic radiation is studied. With the application of the Green function method the expressions of the state vectors and the energies of the stationary states of the system in the regime of the optical resonance are derived. The Rabi oscillations of the electron populations at different levels as well as the Rabi splitting of the peaks in the photon emission spectra are investigated.PACS numbers: 71.35.-y, 78.55.-m, 78.67.Hc